2005
DOI: 10.1097/00000542-200501000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Protects against Myocardial Infarction during Early Reperfusion by Activation of Phosphatidylinositol-3-Kinase Signal Transduction: Evidence for Anesthetic-induced Postconditioning in Rabbits

Abstract: Background: Brief episodes of ischemia during early reperfusion after coronary occlusion reduce the extent of myocardial infarction. Phosphatidylinositol-3-kinase (PI3K) signaling has been implicated in this "postconditioning" phenomenon. The authors tested the hypothesis that isoflurane produces cardioprotection during early reperfusion after myocardial ischemia by a PI3K-dependent mechanism.Methods: Pentobarbital-anesthetized rabbits (n ‫؍‬ 80) subjected to a 30-min coronary occlusion followed by 3 h reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
184
0
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 40 publications
12
184
0
6
Order By: Relevance
“…We have previously demonstrated that 1.0 MAC isoflurane administered using this technique produces reductions in myocardial infarct size that are similar to those observed during preconditioning with this volatile anesthetic. 1,5 We have also previously shown that the sample size used in the current investigation is adequate to provide statistically significant differences in infarct size between interventions. 1,5 PD 098059 and rapamycin were dissolved in dimethylsulfoxide and administered intravenously ten minutes before reperfusion.…”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…We have previously demonstrated that 1.0 MAC isoflurane administered using this technique produces reductions in myocardial infarct size that are similar to those observed during preconditioning with this volatile anesthetic. 1,5 We have also previously shown that the sample size used in the current investigation is adequate to provide statistically significant differences in infarct size between interventions. 1,5 PD 098059 and rapamycin were dissolved in dimethylsulfoxide and administered intravenously ten minutes before reperfusion.…”
Section: Methodsmentioning
confidence: 65%
“…[2][3][4][5] This "anesthetic-induced postconditioning" produces reductions in myocardial infarct size that are very similar to those observed during preconditioning with these agents 1,5 and may be clinically relevant because the precise timing of coronary artery occlusion is unknown in the vast majority of patients with acute myocardial infarction. We recently demonstrated that isoflurane-induced postconditioning is mediated by activation of the prosurvival phosphatidylinositol-3-kinase (PI3K)-Akt signaling cascade.…”
Section: Résultats : L'exposition Brève à Une Concentration Alvéolairmentioning
confidence: 83%
See 2 more Smart Citations
“…It has been indicated that the PI3K/Akt signalling pathway has been involved in isoflurane-induced preconditioning 34 and postconditioning. 35 Additionally, apart from rendering the myocardium resistant to I/R injury, preconditioning also potentiates angiogenesis. 36 Hypoxia inducible factor 1 (HIF-1) serves to promote vascular endothelial growth factor (VEGF) gene expression; thus, it ultimately triggers the cascade of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%